Short-Term Clinical Assessment of Hip Hemi-Arthroplasty in 11 Dogs - Huggard, Renée; Wicks, Grace; Corfield, Gordon (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to assess the short-term clinical outcome in dogs following a hip hemi-arthroplasty for the treatment of primary pathological disorders of the hip and as a salvage procedure following failure of the cup component of a total hip replacement.Study Design Medical records of dogs that had a unilateral hip hemi-arthroplasty performed between 2015 and 2020 were reviewed. Data collected included follow-up orthopaedic examinations performed at 0, 2, 8 and 52 weeks postoperatively, pelvic radiography at 0, 8 and 52 weeks postoperatively and an owner questionnaire (Helsinki chronic pain index [HCPI]).Results Eleven unilateral hip hemi-arthroplasty procedures were identified. The median age at time of surgery was 3.6 years (8 months–10 years) and the median follow-up time was 13 months (range: 2 months–3 years). The HCPI for all dogs at follow-up was median 8 ± 7.30 (range: 5–25). Total HCPI was < 12 for 7/10 dogs and ≥ 12 for 3 dogs. Pelvic radiographs at 1 year confirmed osteointergration of the femoral stem implant and no evidence of implant subsidence or progression of osteoarthritis. However, there was some evidence of mild lucency of the acetabular bed around the prosthetic femoral head and mild peri-acetabular sclerosis in four cases.Conclusion Hip hemi-arthroplasty provides a clinically acceptable treatment for disabling disease of the coxofemoral joint with 10/11 patients achieving acceptable short-term clinical function. Long-term assessment of the hip hemi-arthroplasty and comparison with total hip replacement is indicated.
Keywords: total hip replacement; total hip arthroplasty; hip; hemi-arthroplasty; dog